Electrocardiographic characteristics of patients with chronic obstructive pulmonary disease and its correlation with disease severity - Jatav, Vinod Singh; Meena, S. R.; Jelia, Shivcharan; Jain, Pankaj; Ajmera, Devendra; Agarwal, Vinit; Dayma, Chirangee L.; Arif, Mohd. (International Journal of Advances in Medicine, 2017)
Background: Chronic obstructive pulmonary disease is the fourth leading cause of mortality worldwide. It is defined as a disease state characterized by airflow limitation that is not fully reversible. Patients with chronic obstructive pulmonary disease (COPD) are at increased risk of cardiovascular disease. Electrocardiography (ECG) carries information about cardiac disease and prognosis in COPD patients. Present study was undertaken to correlate ECG changes with severity of COPD. Methods: 100 patients of COPD fulfilling the inclusion criteria coming to OPD/wards of NMCH, Kota were recruited. They were staged by pulmonary function test (PFT) and evaluated by electrocardiography. Statistical analysis of correlation was done with chi square test and statistical significance was taken p<0.05. Results: Mean age was 63.18±8.66 years, with male preponderance, male to female ratio 6.14:1. Mean duration of disease was 7.58±2.92 years, mean exposure to smoking of 25.06 pack years. Most common ECG finding was RAD which was present in 69% of cases, other ECG findings are P. pulmonale (45%), incomplete RBBB (15%), PPRW (35%), RVH (53%). All ECG findings except incomplete RBBB significantly correlated with disease severity (‘p’ value <0.05). Conclusions: COPD is more common in male in 5th to 7th decade of life, with a smoking history of more than 20 pack years. The occurrence of ECG findings increase as severity and duration of disease increase. It can be inferred that ECG is a useful bedside test to assess the severity of COPD.